Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan di BALE UDANG MANG ENGKING Kuta - Ni Kadek Ayu Prihandani; Anak Agung Ketut Sriasih; Ni Luh Komang Julyanti Paramita Sari (Universitas Triatma Mulya, 2024)
This study aims to determine the effect of the work environment and work motivation on employee performance. The location of this research is Bale Udang Mang Engking Kuta. Data collection techniques used are observation, questionnaires and interviews. The population uses employees at Bale Udang Mang Engking Kuta, with a sample of 72 respondents. The data analysis technique used is Descriptive Statistical Analysis, Data Instrument Test, Classical Assumptions, Multiple Linear Regression, t test, Determination and Beta Coefficient. Based on the results of the study, it was found that the work environment has a positive and significant influence on employee performance, work motivation has a positive and significant effect on employee performance, work environment and work motivation have a 58.5% influence on employee performance and work motivation variables have a significant effect more dominant on employee performance. Suggestions that can be given by researchers are to replace lamps that are damaged or unfit for use and have poor lighting, make policies for providing old-age insurance and routinely provide training to employees, provide incentives to encourage employee performance in achieving targets and always help employees if you have problems at work.